Achieving National Food Security in Sub‐Saharan African Countries: The Role of Foreign Agricultural Aid - Mehmet Balcilar; Godwin Olasehinde‐Williams; Berkan Tokar (Food and Energy Security)
ABSTRACT African policymakers have astutely prioritized agricultural expenditure as a crucial strategy to address food insecurity in the continent. However, the available financial resources are insufficient to achieve this objective. Foreign agricultural aid has been proposed as a viable supplement to domestic resource mobilization efforts in bridging the resource deficit. This article investigates the food security implications of sector‐specific aid (agricultural aid) between 1990 and 2020, thus broadening the current understanding. By considering the heterogeneous nature of SSA, this study delves deeper into the relationship between foreign agricultural aid and food security in the region. It investigates both panel and country‐specific causal relationships, providing a more nuanced understanding of the subject. Quantile panel‐type regressions are employed. Coefficients from the fixed effects and random effects with Driscoll–Kraay standard errors are also reported. Additionally, causal linkages between foreign agricultural aid and food security are examined through panel causality testing with bootstrapping. Findings show that agricultural aid contributes to closing the resource gap and improving food security. Also, the effectiveness of agricultural aid is greater when food security is relatively poor, and its impact diminishes as food security improves. Causal relationships suggest that agricultural aid is a determinant of food security. The level of food security is also an indicator of agricultural aid inflows. Thus, strategies such as population control, poverty reduction, and increased access to agricultural land can enhance food security.